Penilaian Produktivitas Kerja Pegawai - Muh. Hizbul Muflihin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
it’s an obligatory to measure individual performance at an organization. From that we will know whether task is conducted by individual, and whether result work productivity. This work productivity measuring is an effort to ensure employee or personal have do their task with certain standards. This evaluation result can be used as basis for reward or punishment. There are several methods to value employee performance, namely Checklist method and Behaviorally Anchored Rating Scale (BARS). Checklist method have simplicity on application, but prone to evaluator bias. Whereas BARS method is more adequate, because based on employee active participation, but not every performance domain can be valued with this method.